Refractory Vasospasm Presenting as Acute Myocardial Infarction - Nismat Javed; Emamuzo Obaro Otobo; Ankita Gore; Maulin Patel; Nisha Ali; Amandeep Singh; Nassim Krim; Preeti Jadhav (Journal of Investigative Medicine High Impact Case Reports)
Refractory coronary artery spasm is a challenging condition with many complications, including acute myocardial infarction. We present the case of an elderly woman who developed refractory coronary artery vasospasm requiring extensive hemodynamic support. She had an abnormal electrocardiogram. She was diagnosed with severe coronary artery vasospasm that initially responded to intracoronary nitroglycerin. However, the course was complicated by arrhythmias and cardiogenic shock following an additional episode of vasospasm that required higher concentrations of nitroglycerin. Notably, this case is relatively less documented in women and within the South Bronx population. Refractory coronary artery spasm is a critical condition that can lead to life-threatening outcomes. Prompt and effective treatment is essential, especially for high-risk patients, to prevent cardiac ischemia. Given the significant dangers of delayed or insufficient treatment, it is crucial to manage coronary artery spasms proactively to enhance patient outcomes and avoid severe complications. In addition, this diagnosis should be strongly considered in women, with an emphasis on following guidelines for managing cases of acute myocardial infarction.